Nanoparticle–membrane interactions - Claudia Contini; Matthew Schneemilch; Simon Gaisford; Nick Quirke (Journal of Experimental Nanoscience, 2018)
Engineered nanomaterials have a wide range of applications and as a result, are increasingly present in the environment. While they offer new technological opportunities, there is also the potential for adverse impact, in particular through possible toxicity. In this review, we discuss the current state of the art in the experimental characterisation of nanoparticle-membrane interactions relevant to the prediction of toxicity arising from disruption of biological systems. One key point of discussion is the urgent need for more quantitative studies of nano-bio interactions in experimental models of lipid system that mimic in vivo membranes.